Long‐Term Outcomes Following Heart Team Revascularization Recommendations in Complex Coronary Artery Disease. Issue 8 (16th April 2019) - Patterson, Tiffany; McConkey, Hannah Z.R.; Ahmed‐Jushuf, Fiyyaz; Moschonas, Konstantinos; Nguyen, Hanna; Karamasis, Grigoris V.; Perera, Divaka; Clapp, Brian R.; Roxburgh, James; Blauth, Christopher; Young, Christopher P.; Redwood, Simon R.; et al.
Abstract : Background: The Heart Team (HT) comprises integrated interdisciplinary decision making. Current guidelines assign a Class Ic recommendation for an HT approach to complex coronary artery disease (CAD). However, there remains a paucity of data in regard to hard clinical end points. The aim was to determine characteristics and outcomes in patients with complex CAD following HT discussion. Methods and Results: This observational study was conducted at St Thomas' Hospital (London, UK). Case mixture included unprotected left main, 2‐vessel (including proximal left anterior descending artery) CAD, 3‐vessel CAD, or anatomical and/or clinical equipoise. HT strategy was defined as optimal medical therapy (OMT) alone, OMT+percutaneous coronary intervention (PCI), or OMT+coronary artery bypass grafting. From April 2012 to 2013, 51 HT meetings were held and 398 cases were discussed. Patients tended to have multivessel CAD (74.1%), high SYNTAX (Synergy between PCI with Taxus and Cardiac Surgery) scores (median, 30; interquartile range, 23–39), and average age 69±11 years. Multinomial logistic regression analysis performed to determine variables associated with HT strategy demonstrated decreased likelihood of undergoing PCI compared with OMT in older patients with chronic kidney disease and peripheral vascular disease. The odds of undergoing coronary artery bypass grafting compared with OMT decreased in the presence of cardiogenic shock and left ventricular dysfunction and increased in younger patients with 3‐vessel CAD. Three‐year survival was 60.8% (84 of 137) in the OMT cohort, 84.3% (107 of 127) in the OMT+PCI cohort, and 90.2% in the OMT+coronary artery bypass grafting cohort (92 of 102). Conclusions: In our experience, the HT approach involved a careful selection process resulting in appropriate patient‐specific decision making and good long‐term outcomes in patients with complex CAD.